Effect of green manure incorporation on yield of subsequent groundnut crop: Effect of green manure incorporation on yield of subsequent groundnut crop - S THIRUVARASSAN; M KUMAR (Journal of Oilseeds Research, 2023)
Field experiments were carried out during 2019 to 2021 at Oilseeds Research Station, Tindivanam to Study the effect of green manure incorporation on yield of subsequent groundnut crop. The result revealed that higher mean pod yield of (2710 kg/ha) was recorded in the treatment (M2 S3) Sunhemp incorporation with 75% RDF application. The pod yield was on par with the green manure crop daincha incorporated with 75 % RDF (M3S3). The treatment control recorded the lowest yield.